Genetic Diversity, Population Structure and Demographic History of Orange Mud Crab Scylla Olivacea from the Bay of Bengal, Bangladesh and Adjacent Seas in the Northern Indian Ocean Based on Mitochondrial COI Gene Sequences (Journal of Science and Technology Research, 2023)
In this study, we analyzed mitochondrial COI gene sequences to reveal genetic diversity, population structure and demographic history of two Bangladeshi (BD) populations (SB and CK) of the orange mud crab Scylla olivacea of the Northern Bay of Bengal (BoB), and compared these two with other four populations in the Northern Indian Ocean region (Arabian Sea, Andaman Sea and Malacca strait) and South China Sea. For all of the populations, nucleotide diversities were low (0.005–0.01) while the haplotype diversities were as high as 0.70–0.96, indicating that the S. olivacea has undergone a recent population expansion after experiencing bottleneck. The pairwise population statistics (FST) revealed that no genetic variation was made between SB and CK populations of BD in BoB. However, these two BoB populations showed separate genetic structure with each of the Andaman Sea (Myanmar coast, MM) and Malacca strait (West coast of Malaysia, MS) populations. On the other hand, two BoB populations did not form separate genetic structure from the population of Arabian Sea (AS). Larval dispersal-based migration by the East and West India coastal currents probably caused this genetic homogeneity between BoB and AS populations.The MM population had separate genetic structure from all of the populations studied in the present study. The Hierarchical analysis of molecular variance (AMOVA) revealed four large population groups of S. olivacea within its distribution range in the Indo-west Pacific region namely, Arabian Sea, Bay of Bengal, Andaman Sea and South China Sea groups. Some geographical barriers (e.g. Indian peninsula, Andaman and Nicobar Islands) along with seasonally formed marine gyres in the Andaman Sea are responsible for separate genetic structure among different populations and also for establishing four population groups. Star-shaped patterns of haplotype network and neutrality test corroboratethe recent population expansion of all populations except MM and CK. Mismatch distribution analysis reveals that the demographic expansion of the species started during the late Pleistocene period approximately 125,000 to 365,000 years ago. These results will help to establish the conservation and management strategy for orange mud crab in the Northern Indian Ocean region including the Bay of Bengal.J. of Sci. and Tech. Res. 4(1): 101-118, 2022